Inferior vena cava diameter determines left ventricular geometry in continuous ambulatory peritoneal dialysis patients: an echocardiographic study - KOÇ, MEHMET (OXFORD UNIV PRESS, 2003)
Background. Changes in left ventricular (LV) geometry are frequent in patients with continuous ambulatory peritoneal dialysis (CAPD). Geometric adaptation of LV to various stimuli was reported to have adverse prognosis. This study aimed to identify independent risk factors, which contribute to the development of LV geometric remodelling in CAPD patients. Methods. The left ventricles of 69 CAPD patients were classified echocardiographically into four different geometric patterns on the basis of LV mass and relative wall thickness. With respect to volume factor, we measured inferior vena cava (IVC) diameter and its decrease on deep inspiration [collapsibility index (CI)] by echocardiography. We modelled a stepwise multiple regression analysis to determine the predictors of LV geometry. Results. All four geometric models of LV were identified in our group of 69 CAPD patients. Eccentric left ventricular hypertrophy (eLVH) was observed in 32 (46%), concentric LVH (cLVH) in 19 (28%), normal geometry (NG) in 10 (14%) and concentric remodelling (CR) in eight (12%) CAPD patients. Mean IVC index of the eLVH group (10.72 +/- 2.19 mm/m(2)) was significantly higher than corresponding indexes of NG (7.90 +/- 1.54 mm/m(2)), CR (8.51 +/- 1.28 mm/m(2)) and cLVH (8.04 +/- 2.00mm/m(2)) groups (P < 0.001 for each comparisons). The eLVH group also had significantly lower mean CI value (0.48 +/- 0.11) than CR (0.58 +/- 0.09) and cLVH (0.57 +/- 0.07) groups (ANOVA P=0.008). Stepwise multiple regression analysis revealed that IVC index, CI and haemoglobin were the independent predictors of LV geometric stratification (R-2 =0.36, P < 0.001). Conclusion. Hypervolaemia, identified by IVC index and CI, and anaemia contribute independently to LV geometry in CAPD patients. Echocardiography as a non-invasive tool is not only useful to determine LV geometry, but also to assess the volume status of CAPD patients.
Keywords: continuous ambulatory peritoneal dialysis; inferior vena cava; ventricular remodelling; DRY-WEIGHT; HEMODIALYSIS; HYPERTROPHY; MORBIDITY; MORTALITY; PATTERNS; VOLUME; IMPACT; MASS